1990
DOI: 10.4141/cjss90-016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potato Cropping Practices on Water Runoff and Soil Erosion

Abstract: Using runoff-erosion plots (10 m wide × 30 m long), the effects of cropping practices on surface runoff and soil loss were examined on a Hommesville gravelly loam soil to evaluate the applicability of the Universal Soil Loss Equation in New Brunswick. The amount of water runoff and soil loss from continuous fallow, up-and-down slope planting of potatoes (Solanum tuberosum), and clover (Trifolium pratense) on 8 and 11% slopes were measured from 1983 to 1985. In addition, runoff and soil loss from contour planti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
35
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 0 publications
7
35
1
Order By: Relevance
“…This amount represents approximately 42% of the total erosivity value during the cropping season of 1990. This is consistent with Chow et al (1990) who reported that a major proportion of the erosivity resulted from a relatively small number of severe rainstorms. Similarly, Epstein et al (1966) reported that 20 out of 240 storms resulted in 75% of the total soil loss and 55% of the total runoff during 1961-1964 in Northeastern Maine.…”
Section: Weather Informationsupporting
confidence: 81%
“…This amount represents approximately 42% of the total erosivity value during the cropping season of 1990. This is consistent with Chow et al (1990) who reported that a major proportion of the erosivity resulted from a relatively small number of severe rainstorms. Similarly, Epstein et al (1966) reported that 20 out of 240 storms resulted in 75% of the total soil loss and 55% of the total runoff during 1961-1964 in Northeastern Maine.…”
Section: Weather Informationsupporting
confidence: 81%
“…Although the magnitude of soil loss rates were considerably different from year to year, the proportional reductions in soil loss were very similar. Nonlinear relationships between runoff and soil loss have been reported by Wischmeier (1966) and Chow et al (1990).…”
Section: Rate Of Runoff and Soil Lossmentioning
confidence: 95%
“…Water erosion is particularly severe in the ''Potato Belt'' in north western NB (Coote et al 1982;Chow et al 1990). In a comparison of cultivated agricultural lands versus virgin forested profiles in north western NB, Wang et al (1984) estimated that there was an 8 cm reduction in soil solum thickness.…”
mentioning
confidence: 99%